Co-producing an intervention to reduce sedentary behaviour in community-dwelling older adults aged ≥ 75 informed by behaviour change theory - Ragy Tadrous; Anne Forster; Amanda Farrin; Peter A. Coventry; Andrew Clegg (BMC Geriatrics)
Abstract Background Older adults are the fastest-growing and most sedentary group in society. With sedentary behaviour associated with negative health outcomes, reducing sedentary time may improve overall well-being. Adults aged ≥ 75 years are underrepresented in sedentary behaviour research, and tailored strategies to reduce sedentary time may be warranted. The development of an intervention to reduce sedentary behaviour in adults aged ≥ 75 years using co-production and behaviour change theory is reported. Methods Four co-production workshops with community-dwelling older adults aged ≥ 75 years were held between October-December 2022. The intervention development process was informed by the Behaviour Change Wheel (BCW) and Theoretical Domains Framework (TDF). Audio recordings and workshop notes were iteratively analysed, with findings used to inform subsequent workshops. Results The co-production group consisted of six community-dwelling older adults aged ≥ 75 years and two researchers. The developed intervention consists of four components (activity monitoring, educational material, group sessions and researcher follow-up), maps to 24 behaviour change techniques and targets barriers to reducing sedentary time. Participants were receptive of the co-production process. Conclusions Integrating co-production with the BCW can provide several benefits, with the BCW providing structure to the intervention development process, and co-production increasing the likelihood of the developed intervention being viewed as feasible by older adults. Furthermore, coding intervention components to the BCW may further our understanding of what approaches are successful at influencing behavioural change. Transparent reporting of the intervention development process may benefit researchers developing interventions with older adults. Future research will pilot the co-produced intervention.